The Impact of Regional Fiscal Factors and Labor Force Participation on Poverty - Rafella, Reva; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2026)
Poverty remains a challenge both globally and locally, including in Indonesia, where Central Java ranks second after Yogyakarta. This condition is influenced by regional development disparities and limited fiscal capacity. The government seeks to address these issue by strengthening regional financial instruments such as intergovernmental transfers, village funds, and fiscal independence. Data on the realization of intergovernmental transfers and village funds in Central Java regencies for period 2017-2024 indicate optimal absorption, however poverty levels remain high. Moreover, non-fiscal factors, particularly the Labor Force Participation Rate (LFPR), play an important role in alleviating poverty by enhancing productivity and overall community welfare. This study adopts a quantitative causal approach using secondary data obtained from DJPK and BPS. Panel data regression is employed as the analytical technique, with model selection conducted through the Chow Test, Hausman Test, and Lagrange Multiplier Test. The regression results are further assessed using the t-test, F-test, and coefficient of determination. Based on relevant theories and previous empirical studies, this research hypothesizes that all independent variables have a negative and statistically significant on poverty levels.